2019
DOI: 10.14715/cmb/2019.65.3.9
|View full text |Cite
|
Sign up to set email alerts
|

The concurrent effect of acyclovir and rosemary on glioblastoma cell culture

Abstract: Human cytomegalovirus (HCMV) is a beta herpesvirus which large amount of people in world has interacted with. Recent studies indicated that CMV DNA is associated with several cancer types including "Glioblastoma (GBM)" which is the most common and aggressive type of primary brain cancer. In clinical studies it was shown that several antiviral medicines prolonged life span of glioblastoma patients. One of them is Acyclovir (ACV) which is a type of nucleoside analog, used to cure viral infections and might be a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…Our results agree with other reports that confirmed the cytotoxic effect of Rosemary leaves extracts on different cancer cell lines [AGS – human gastric carcinoma, KYSE 30 – human esophageal squamous cell carcinoma, HT-29 – colon adenocarcinoma; (GBM) U87 MG – glioblastoma] [ 55 , 56 , 57 ]. Other authors reported cytotoxic activity of O. vulgare essential oil and its main constituents (carvacrol, thymol, limonene) on hepatocellular carcinoma cell line (HepG2) [ 20 ].…”
Section: ⧉ Discussionsupporting
confidence: 93%
“…Our results agree with other reports that confirmed the cytotoxic effect of Rosemary leaves extracts on different cancer cell lines [AGS – human gastric carcinoma, KYSE 30 – human esophageal squamous cell carcinoma, HT-29 – colon adenocarcinoma; (GBM) U87 MG – glioblastoma] [ 55 , 56 , 57 ]. Other authors reported cytotoxic activity of O. vulgare essential oil and its main constituents (carvacrol, thymol, limonene) on hepatocellular carcinoma cell line (HepG2) [ 20 ].…”
Section: ⧉ Discussionsupporting
confidence: 93%
“…The combination of rosemary and acyclovir reduced the survival by 10% more. A 52.7% reduction in the viability of GBM was seen in the acyclovir group (Özdemir and Göktürk, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…The first enzyme is involved in developing immunosuppressive lymphocytes and immunologic tolerance in the tumour microenvironment (Godin-Ethier et al, 2011); the latter is involved in the targeted degradation of various growth and survival factors via ubiquitin-mediated pathway (Frescas and Pagano, 2008). Accordingly, the in vitro suppressive effect of ACV on MCF-7 breast cancer cells, Jurkat leukaemia cells, and U87 MG glioblastoma cells has been recently reported (Shaimerdenova et al, 2017;Benedetti et al, 2018;Özdemir and Göktürk, 2019), demonstrating ACV ability to affect cancer cell viability and sustaining its potential as adjuvant therapy in cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The relevant biochemical mechanisms by which ACV may induce anticancer effects even without the detection of HHVs (Benedetti et al, 2018;Özdemir and Göktürk, 2019) that could mediate the intracellular phosphorylation of ACV via viral kinases rendering it capable of blocking DNA synthesis (Schaeffer, 1982;Elion, 1993), are still poorly understood. Early studies showed that low detectable phosphorylated ACV levels could be present within cells even in the absence of viral thymidine kinases (McMahon et al, 2011), indicating that endogenous kinases could phosphorylate the drug.…”
Section: Introductionmentioning
confidence: 99%